Interactive flood hazard visualisation in Adobe Flash. (30th September 2015) - Coller, M.L.F.; Wheeler, P.; Kunapo, J.; Peterson, J.
Abstract: Advances in analytical flood modelling need to be accompanied by similar advances in the means by which model results can be disseminated across a wide range of stakeholder groups. In this paper, we exemplify the use of Adobe Flash as a means to design interactive flood mapping methods that can portray a wide range of potential flood levels, and place them into a context of flood frequency. We apply this methodology to a coastal flood‐prone locality in Australia, integrating a range of flood‐related information into a single intuitive interface. We demonstrate how a temporal dimension can be incorporated to represent future changes to inundation probability based on climate change projections of sea‐level rise. The resulting visualisation is accessible directly via the web, and is designed for ease of use and understanding for all stakeholders. Such flexible methods of representing flood hazard can foster education on flood issues, support community decision‐making and assist emergency response when floods eventuate. In this way, such mapping methods can play a vital role in integrated coastal zone management initiatives.